Seroresponses and safety of 13‐valent pneumococcal conjugate vaccination in kidney transplant recipients. Issue 2 (1st April 2018) - Dendle, Claire; Stuart, Rhonda L.; Polkinghorne, Kevan R.; Balloch, Anne; Kanellis, John; Ling, Johnathan; Kummrow, Megan; Moore, Chelsea; Thursky, Karin; Buttery, Jim; Mulholland, Kim; Gan, Poh‐Yi; et al.
Abstract: Background: Conjugated pneumococcal vaccine is recommended for kidney transplant recipients, however, their immunogenicity and potential to trigger allograft rejection though generation of de novo anti‐human leukocyte antigen antibodies has not been well studied. Methods: Clinically stable kidney transplant recipients participated in a prospective cohort study and received a single dose of 13‐valent conjugate pneumococcal vaccine. Anti‐pneumococcal IgG was measured for the 13 vaccine serotypes pre and post vaccination and functional anti‐pneumococcal IgG for 4 serotypes post vaccination. Anti‐human leukocyte antigen antibodies antibodies were measured before and after vaccination. Kidney transplant recipients were followed clinically for 12 months for episodes of allograft rejection or invasive pneumococcal disease. Results: Forty‐five kidney transplant recipients participated. Median days between pre and post vaccination serology was 27 (range 21‐59). Post vaccination, there was a median 1.1 to 1.7‐fold increase in anti‐pneumococcal IgG antibody concentrations for all 13 serotypes. Kidney transplant recipients displayed a functional antibody titer ≥1:8 for a median of 3 of the 4 serotypes. Post vaccination, there were no de novo anti‐human leukocyte antigen antibodies, no episodes of biopsy proven rejection or invasive pneumococcal disease. Conclusion: A single dose of 13‐valent conjugate pneumococcal vaccine elicits increased titers and breadth of functional anti‐pneumococcal antibodies in kidney transplant recipients without stimulating rejection or donor‐specific antibodies.